Social Origin and Parental and Offspring Union Dissolution: Cues from Sibling Correlations - Linus Andersson (Suomen akatemia, 2022)
This paper estimates the size of the effect of parental union dissolution on offspring union dissolution, as a share of the sum of all social origin factors. A large literature has documented a positive correlation between divorce and separation among parents and their children. Parental union dissolution is one out of several aspects of social origin that is associated with union dissolution. It is difficult to contrast the relative impact of parental union dissolution to other aspects of social origin because many apects of social origin are unobservable. Swedish administrative data for the 1960 to 1965 birth cohorts that cover the individuals’ life events until 2018 is used to estimate sibling correlations in divorce and childbearing union dissolution, adjusting for parental union dissolution. The variance in union dissolution attributable to factors shared by siblings ranged from 6% to 13%. Parental union dissolution and factors associated with parental union dissolution explained between 15% and 28% of this variance. Sister correlations are greater than brother correlations, and sibling correlations of childbearing union dissolution are higher than sibling correlations of divorce. It is pertinent to estimate the total effect of all social background factors on offspring union dissolution. It is likewise of interest to specify the share of all social background effects that are constituted by factors caused by or correlated specifically with parental union dissolution. Sibling correlations can be a useful tool for quantifying these relationships.